ASSOCIATION BETWEEN OBESITY AND PERMANENT TOOTH ERUPTION - Plamena Sapunarova; Tanya Nihtyanova; Svetla Petrova; Maria Kukleva (Peytchinski Publishing, 2020)
Purpose: Obesity is a significant health risk of modern society, which prevalence has dramatically increased and affects children at a lower and lower age. The aim of the study is to investigate the effect of obesity on permanent tooth eruption timing. Material/Methods: A cross-sectional study was performed in Plovdiv, October-December 2017 and January-March 2018, among 1826 school children aged 6-11. Dental examination was executed in the schools' medical rooms, using sterile dental kit and flashlight. The number of erupted permanent teeth (NET) was evaluated considering all in the process of eruption and fully erupted permanent teeth. Data for BMI was collected, and statistical analysis was done. Descriptive statistics, ANOVA, single and multiple linear regression and Chi-square test of independence were used to test the Null hypothesis. Results: The underweight children were 8.3%, normal weight - 65.8%, overweight 15.6% and 10.3% were obese. There was no significant correlation between gender, age and BMI:x2(3) =4.862, p>0.05; x2(18) =12.451 p>0.05, N=1826. Simple linear regression showed statistical significance of the model, F=166,318p<0.0001, and positive correlation between BMI and NET, B=0,441 where 1% (R2=0,084) of the variation in the NET was explained by BMI. A multiple linear regression, where age and gender were included as explanatory variables, showed that all factors were significantly associated with NET (BMI: B= 0.213; Age: B= 2.662; Gender: B=1.011 p<0.0001). Conclusions: Increased BMI and being female is associated with accelerated permanent tooth eruption.